2022
DOI: 10.1108/jhom-04-2022-0106
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers' autonomy: testing the reciprocal relationship between job autonomy and self-leadership and moderating role of need for job autonomy

Abstract: PurposeWhile both perceived job autonomy and self-leadership are assumed to be important for optimal functioning of healthcare workers, their mutual relationship remains unclear. This cross-lagged study aims to theorize and test that perceived job autonomy and self-leadership have a reciprocal relationship, which is moderated by need for job autonomy.Design/methodology/approachTwo-wave panel data were used to measure cross-lagged relationships over a time period of three months. Self-leadership is indicated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 86 publications
(269 reference statements)
0
2
0
Order By: Relevance
“…In this study, nurse managers highlighted the importance of continuing training related to nursing work, but no mention was made of training related to self‐leadership or systematic work development, which would be especially important to increasing professional autonomy. Self‐leadership skills give nurses the readiness to act autonomously and take more responsibility at work (van Dorssen‐Boog et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, nurse managers highlighted the importance of continuing training related to nursing work, but no mention was made of training related to self‐leadership or systematic work development, which would be especially important to increasing professional autonomy. Self‐leadership skills give nurses the readiness to act autonomously and take more responsibility at work (van Dorssen‐Boog et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have pointed out that investments have been targeted at nurses' early career development but not in the middle or later phases of their careers (Beal & Riley, 2019). To experience professional autonomy, nurses must be supported by their managers and simultaneously skilled in self‐leadership which means that they proactively direct themselves towards optimal performance and take responsibility for their own actions (van Dorssen‐Boog et al, 2022). However, it must be noted that the profession and rights of nurses are defined by law, and they also create the framework for the discussion about nurses' autonomy (ICN, 2013; Grinberg & Sela, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While self-leadership can be promoted through autonomy-supportive climates (Stewart et al 2019 ), individuals must have self-leadership attributes to achieve autonomy (Hasugian, Simamora & Gaol 2021 ). It is when a self-leading individual works within an autonomy-supportive climate that feelings of meaning, competence and self-determination are experienced (Van Dorssen-Boog et al 2022 ). According to Liao et al ( 2022 ), self-leading individuals’ inclinations to be innovative, risk-takers and proactive are better leveraged in an autonomy-supportive climate.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have observed that self-leadership practices thrive in climates that support autonomy, thus boosting self-leadership skills and self-confidence (Nientied & Toska 2021 ; Ralph et al 2020 ). While self-leadership is an internal process, external forces such as an autonomy-supportive climate can positively influence the practicing of self-leadership (Van Dorssen-Boog et al 2022 ). This is because an autonomy-supportive climate enhances feelings of meaningfulness, competence and self-motivation to perform well in all spheres of one’s work activities, whether operational, administrative or strategic activities, leading to organisational success (Van Dorssen-Boog et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Job autonomy was discovered to favor innovative conduct by enhancing intrinsic motivation, prompting individuals to explore diverse concepts and approaches for enhanced imaginative issue-solving within assigned duties (Lee et al, 2021). Breaugh (1985) identifies job autonomy as an opportunity given by the organization to its employees to plan work assignments independently (work scheduling), the freedom to decide how to carry out the given work tasks (work methods), as well as choose goals and determine the priority scale of tasks in work (autonomy criteria) (van Dorssen-Boog et al, 2022).…”
Section: Introductionmentioning
confidence: 99%